AB0310 Prospective Study of 78 Patients Treated with Infliximab Biosimilar Remsima®. (15th July 2016) - Rubio, E.; Ruiz, A.; Lόpez, J.; Lόpez-Chozas, J.M.; Bermudez, L.; Aguilera, C.; Povedano, J.
Abstract : Background: In 2015 it began to be used in many EU countries the first biosimilar antiTNF (Infliximab) approved by the EMA. The Korean company owns the molecule under the trademark Remsima® was widely used for replacing existing treatments with infliximab molecule marketed since 1999 as Remicade in the approved indications in sheet for this purpose, RA, AS and PsA. Objectives: Control the security and survival of the drug in patients Remsima® in which replaced the molecule Remicade infliximab. Settled visits every 3 months to monitor the occurrence of adverse events with possible association to the drug. Patients were followed in routine clinical practice for 8 different doctors. Methods: 78 patients began treatment with Remsima® since March 2015. Of these, 25 were suffering from Rheumatoid Arthritis, Psoriatic Arthritis 8, SpA 41 and severe uveitis 2. 53 of these patients had already been treated with Remicade and 25 were "naive" to IFX, having been previously treated with other biological therapy or were naive to this. Results: 37 patients, less than half have associated a DMARD in the 9th month of follow-up (70'2% MTX). 11 patients with Remsima not reached 37 weeks of follow-up and were removed (5 of these patients had replaced Remicade). None of them was removed for serious adverse effect. Overall 86% survival at 9 months. No patient dropped the sheet approved for disease Remsima 3mg/kg body weight or Remsima 5mg/kg dose before 6 months of treatment. The reasons for medication discontinuation were in the 5 cases of replacement Remicade by Remsima: 4 loss efficacy and cutaneous leishmaniasis. For patients naive to Remicade, 1 case of possible photosensitivity, 1 case of bronchospasm during infusion, one case of urticaria, 1 case of hip replacement surgery, one transfer to another country of residence and a loss of effectiveness. The reasons for medication discontinuation were in the 5 cases of replacement Remicade by Remsima: 4 loss efficacy and cutaneous leishmaniasis.For patients naive to Remicade, 1 case of possible photosensitivity, 1 case of bronchospasm during infusion, one case of urticaria, 1 case of hip replacement surgery, one transfer to another country of residence and a loss of effectiveness. 4 patients showed in repeated infusions dizziness, headache or neck stiffness within 48 hours of infusion Remsima. However they asked to continue with medication. Overall 86% survival at 9 months.Only 23% of patients needed glucocorticoid use at 9 months. 22% of patients required to reduce the infusion period IFX-Remsima 7 weeks or less. Finally in 4 patients an optimization of treatment extending to more than 8 weeks was achieved infusions. It is worth drawing attention to the small variation of CRP level (Δ <5mg/dl) at 9 months of initiation of Remsima treatment. Conclusions: The results of safety and survival of biosimilar infliximab Remsima® are similar to those shown in their pivotal trials PLANETRAS and PLANETAS, both in patients with prior use of infliximab as another patient who has not used this. Although the follow-up period is too short, averaging 8.3 months and a standard deviation of 2, these data support an increasingly widespread use of this biosimilar in any patient profile. Disclosure of Interest: None declared